Client and provider factors associated with integration of family planning services among maternal and reproductive health clients in Kigoma Region, Tanzania: a cross-sectional study, April-July 2016 - M. M. Dynes; E. Bernstein; D. Morof; L. Kelly; A. Ruiz; W. Mongo; P. Chaote; R. N. Bujari; F. Serbanescu (BMC, 2018)
Abstract Background Integration of family planning (FP) services into non-FP care visits is an essential strategy for reducing maternal and neonatal mortality through reduction of short birth intervals and unplanned pregnancies. Methods Cross-sectional surveys were conducted across 61 facilities in Kigoma Region, Tanzania, April-July 2016. Multilevel, mixed effects logistic regression analyses were conducted on matched data from providers (n = 330) and clients seeking delivery (n = 935), well-baby (n = 272), pregnancy loss (PL; n = 229), and other routine (postnatal, HIV/STI, other; n = 69) services. Outcomes of interest included receipt of FP information and a modern FP method (significance level p < 0.05). Results Clients had significantly greater odds of receiving FP information if the primary reason for seeking care was for PL versus (vs) any other types of care (aOR 1.97), had four or more pregnancies vs fewer (aOR 1.78), and had had a FP discussion with their partner vs no FP discussion (aOR 1.73). Clients had lower odds of receiving FP information if they were aged 40-49 vs 15-19 (aOR 0.50) and reported attending religious services at least weekly vs less frequently (aOR 0.61). Clients of providers who perceived that in-service training had helped vs had not helped job performance (aOR 2.27), and clients of providers having high vs low recent FP training index scores (aOR 1.58) had greater odds of receiving FP information. Clients had greater odds of receiving a modern method when they received information on two or more vs fewer methods (aOR 7.13), had had a FP discussion with their partner vs no discussion (aOR 5.87), if the primary reason for seeking care was for PL vs any other types of care (aOR 4.08), had zero vs one or more live births (aOR 3.92), made their own FP decisions vs not made own FP decisions (aOR 3.17), received FP information from two or more vs fewer sources (aOR 3.12), and were in the middle or high vs the low wealth tercile (aOR 1.99 and 2.30, respectively). Well-baby care clients, Other routine services clients, and married clients had significantly lower odds of receiving a method (aOR 0.14; aOR 0.08; and aOR 0.41, respectively) compared to their counterparts. Conclusions Strategies that better integrate FP into routine care visits, encourage women to have FP discussions with their partners and providers, increase FP training among providers, and expand FP options and sources of information may help reduce the unmet need for FP, and ultimately lower maternal and neonatal mortality.